Perencanaan Strategis Sistem Informasi/ Teknologi Informasi pada Pusat Koperasi Industri Susu (PKIS) XYZ - Chayadi Oktomy Noto Susanto; Tutut Wurijanto; Tony Soebijono (Universitas Muhammadiyah Yogyakarta, 2015)
Corporate awareness of the importance of technology’s support in supporting efficiently and effectively business activities is increase. It is also being pursued by PKIS XYZ to manage their business activities. PKIS XYZ experiencing problems which only able to manage 33,33% of their raw materials, while the rest should be managed by another company which incidentally is their competitor. This is certainly not profitable for the company. This research will analyse business processes in PKIS XYZ which are not optimal implemented. The findings obtained will be used as a material planning what technology to be applied in an attempt to optimize the business activities of the company. The output of this research is recommendation of future application portfolio that important to be applied in PKIS XYZ. Framework used in this study was Ward and Peppard, with SWOT and Mc Farland's Strategic as a tool.